The Role of Law Enforcement Officers in Eradicating Online Gambling - Suwandi Suwandi; Bunga Amalia Nasution (Program Pascasarjana UIN Sumatera Utara Medan, 2022)
Online gambling is a form of cybercrime that has experienced rapid growth along with advances in information and communication technology in Indonesia. This phenomenon not only impacts the legal aspects but also creates social and economic problems in society. This study aims to analyze the role of law enforcement officials in eradicating online gambling practices and identify obstacles faced in the law enforcement process. The research method used is normative juridical, with a statutory regulatory approach and literature review. The results indicate that law enforcement officials play a crucial role through preventive and repressive measures, such as website blocking, investigations, arrests, and prosecutions based on the provisions of the Criminal Code and the Information and Electronic Transactions Law. However, various obstacles remain in its implementation, including technological limitations, the transnational nature of the crime, and a lack of coordination between institutions. Therefore, stronger synergy is needed between the government, law enforcement officials, and the public to increase the effectiveness of eradicating online gambling in Indonesia.